See the proof belowExplanation:We need \displaystyle\cotx=\frac\cosx\sinx\displaystyle\cscx=\frac1\sinx Therefore, \displaystyleLHS=\frac\cotx\cscx ...


You are watching: Cos x csc x cot x

watch belowExplanation: \displaystyle\cosx=\frac\cotx\cscx ideal Side: \displaystyle=\frac\cotx\cscx\displaystyle=\frac\frac\cosx\sinx\frac1\sinx ...
\displaystyle\frac1+\cscx\cosx+\cotx=\secx Explanation:We will be making use of the adhering to identities: \displaystyle\cscx=\frac1\sinx\displaystyle\cotx=\frac\cosx\sinx ...
*
*
*

\left< \beginarray l l 2 & 3 \\ 5 & 4 \endarray \right> \left< \beginarray together l together 2 & 0 & 3 \\ -1 & 1 & 5 \endarray \right>
*
*

*
*

*
*



See more: What Do You Need Neutralizing Shampoo After Bleaching Hair, How To Wash Bleach Out Of Hair Like A Pro

EnglishDeutschEspañolFrançaisItalianoPortuguêsРусский简体中文繁體中文Bahasa MelayuBahasa Indonesiaالعربية日本語TürkçePolskiעבריתČeštinaNederlandsMagyar Nyelv한국어SlovenčinaไทยελληνικάRomânăTiếng Việtहिन्दीঅসমীয়াবাংলাગુજરાતીಕನ್ನಡकोंकणीമലയാളംमराठीଓଡ଼ିଆਪੰਜਾਬੀதமிழ்తెలుగు